The prevalence and association of measured and perceived indoor air quality, housing characteristics, and residents’ behavior and health - Charlotte Gabel; Torben Sigsgaard; Steffen Petersen; Grethe Elholm (Frontiers in Environmental Health, 2024)
BackgroundIn social housing buildings, poor indoor air quality (IAQ) has been shown to be more prevalent, and residents living in social housing areas are often more vulnerable and susceptible to adverse health effects from IAQ.AimTo examine the state and the association of measured and perceived IAQ, how housing characteristics and residents' behavior are associated with IAQ, and the association with residents' health.MethodThe HOME-Health study is a cross-sectional study among residents living in social housing in Denmark (n = 432). Seasonal measurements examined the IAQ by a 14-day period measuring carbon dioxide (CO2), temperature (TP), relative humidity (RH), and air change rate. Residents' self-reported behavior, comfort, and health were obtained from a structured interview.ResultsThermal discomfort and draught were the most common challenges. During summer, the mean TP was higher, the mean RH was lower, and residents more frequently reported dry air in homes where it was not possible to create cross ventilation. There were a higher mean CO2 and RH when crowdedness increased, particularly during winter. In addition, the proportion of residents reporting dry air was higher when CO2-level was below 1,000 ppm. When the mean RH-level was above 50%, a higher proportion of residents reported experiencing damp air, and when the mean RH-level was below 40% residents more frequently reported dry air. Perception of bad air quality was higher when the mean CO2-level exceeded 1,000 ppm. Additionally, residents reported being most thermally comfortable when the TP was within the range of 20–20.99°C and least comfortable within a range of 22–22.99°C. The residents' perceived experience of impaired IAQ was associated with negative general health symptoms.ConclusionIt is key that homes have the capability to create cross ventilation in order to allow for proper ventilation and to avoid overheating. When evaluating IAQ it is important to not only consider the measured parameters but to also include the residents' behavior and perception of IAQ as these both are related to the actual IAQ and associated health effects.